2018
DOI: 10.2399/jmu.2018001006
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of the relationship between seasonal factors and idiopathic sudden sensorineural hearing loss

Abstract: Özet: ‹klim flartlar› ile idiyopatik ani sensörinöral iflitme kayb› aras›ndaki iliflkinin retrospektif de¤erlendirmesi Amaç: Kendi yaflad›¤›m›z bölgenin iklim flartlar› ve meteorolojik parametrelerin idiyopatik ani sensörinöral iflitme kayb›n›n (ISSNHL) patogenezi ve prognozu üzerinde bir etkisinin olup olmad›¤›n› arafl-t›rmay› amaçlad›k. Yöntem: Bölümümüzde tedavileri yap›lm›fl olan 68 ISSNHL tan›s› olan hasta retrospektif olarak incelendi. Ayl›k ortam s›cakl›¤›, maksimum ve minimum s›cakl›k, ba¤›l nem, atmos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…One study (17) used a 20 dB hearing loss in three consecutive major frequencies over no more than 72 hours as the definition of an SSNHL. Four (reference numbers [20,23,25,26] in Table 1) of the 13 enrolled papers did not provide the criteria used for defining an SSNHL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study (17) used a 20 dB hearing loss in three consecutive major frequencies over no more than 72 hours as the definition of an SSNHL. Four (reference numbers [20,23,25,26] in Table 1) of the 13 enrolled papers did not provide the criteria used for defining an SSNHL.…”
Section: Resultsmentioning
confidence: 99%
“…One study (17) used a 20 dB hearing loss in three consecutive major frequencies over no more than 72 hours as the definition of an SSNHL. Four (reference numbers [20,23,25,26] in Table 1) of the 13 enrolled papers did not provide the criteria used for defining an SSNHL. 15) studies included 45,277, 9,267, and 4,753 cases of SSNHL, respectively, whereas the other studies had between 68 to 320 cases of ISSNHL.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…Some researchers reported a significant relationship between the onset of ISSHL and weather conditions [5,6,19], while others reported no relationship between weather conditions and the development of ISSHL [7,8]. There are limited studies investigating the relationship between ISSNHL prognosis and meteorological factors [7,22]. The relationship between the daily temperature range and the recovery rates of sudden hearing loss remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Narozny et al [17] reported the occurrence of this disease in spring as a positive prognostic factor. Durmuş et al [22] reported a relationship between the average temperature and rainfall before the onset of ISSNHL and the prognosis of ISSNHL.…”
Section: Discussionmentioning
confidence: 99%